If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 7) + -8 = 12 Reorder the terms: (7 + X) + -8 = 12 Remove parenthesis around (7 + X) 7 + X + -8 = 12 Reorder the terms: 7 + -8 + X = 12 Combine like terms: 7 + -8 = -1 -1 + X = 12 Solving -1 + X = 12 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + X = 12 + 1 Combine like terms: -1 + 1 = 0 0 + X = 12 + 1 X = 12 + 1 Combine like terms: 12 + 1 = 13 X = 13 Simplifying X = 13
| 2e^3x=30 | | 24x+2x=3x+48 | | 30X+60-30X=60 | | 30X+30-30X=60 | | X2=36/64 | | 6(7-5x)-5x=252 | | 6x-14=6x+14 | | 11=s/2 | | 4x^3+12x^2+6x-2=0 | | 5=d/8 | | 0.1666666= | | (2n+6)4=-2n+4 | | =X/2*2× | | X/2*2× | | 34=-1/4y | | -4x=-31 | | (X+4)(3x-2)=3x(x+1) | | 42=2/5x-7 | | X-24=3x | | 100=y-16 | | 4(2+5)-3z=5 | | 13(p+2)=-30 | | -x-8=2-3x | | 3x^2-2x+12x-8=3x^2+3x | | 4x+7y=107 | | e^2-7x=834 | | -10-5x^2=-510 | | 7-2x=3-2(x-2) | | X/11=13/8 | | 7-8(4-6x)=-121 | | 2x^4-2x^2-3=0 | | X-5=-5x-41 |